Artificial intelligence and systems theory applied to cooperative robots: the SocRob project - Lima, Pedro (2002)
This paper describes an approach to the design of a population of cooperative robots based on concepts borrowed from Systems Theory and Artificial Intelligence The research has been developed under the SocRob project, jointly carried out by the Intelligent Control and Artificial Intelligence Laboratories at ISR/IST. The acronym of the project stands both for "Society of Robots" and "Soccer Robots", the case study where we are testing our population of four robots. Designing soccer robots is a very challenging problem, where the robots must act not only to shoot a ball towards the goal, but also to detect and avoid static (walls, stopped robots) and dynamic (moving robots) obstacles. Furthermore, they must cooperate to defeat an opposing team. Our current research in soccer robotics includes image processing for object segmentation, recognition and tracking, navigation and behavior-based architectures for real time task execution of cooperating robot teams. Cooperative learning, behavior modeling and distributed planning are topics we have been investigating and plan to apply to soccer robots and other case studies, such as search and rescue robots.